The British American navigator : a sailing directory for the island and banks of Newfoundland, the Gulf and River of St. Lawrence, Breton Island, Nova Scotia, the Bay of Fundy, and the coasts thence to the River Penobscot, etc. - Purdy, John, 1773-1843.; Findlay, Alexander G. (London : Printed for R.H. Laurie, 1847)
Includes index. "Being vol. I of the Sailing directories for the eastern coasts and islands of America." Mode of access: Internet.